Colonial Structure, Chinese Minority and Racial Violence in Indonesia: A Social Reflection - Herdi Sahrasad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Under the Dutch colonial, the Dutch (white skin) become the  political, economic and social elites in the colonial society, while middle class consisted of far east people (Chinese, Arab, India, etc), and bumiputera (indigenous Muslim) people laying in lower layer functioning producer of natural resources or traditional (feodal) elite. Dutch elites (top local officials, such as resident), Chinese elite (officer), and traditional elite (regents) are "Top Branch" of colonial society. The structure has been continuing in the era of Soekarno’s Old Order and Soeharto’s New Order. And under the New Order, the political practices of minority have serious social-political implications related to negative image that always inherent in Tionghoa (Chinese) people of Indonesia. The Indonesian Chinese (Tionghoa) often be assumed as source of various problems, simply could be ‘scapegoat’, if there are riots, economic crisis and racialism. Under the New Order, the Indonesian Chinese remain to treated as the others, the marginalized people. In the post Soeharto’s New Order 1998, however, the Chinese have been awakening gradually to join political parties and social organizations to take part in democratization and governance, even most of the Chinese conglomerates (taipan) has been the richest in Indonesia.